Iptek Bagi Masyarakat (IBM) Pemanfaatan Teknologi Tepat Guna (TTG) Pada Kelompok Masyarakat Pembuat Lakso Di Kabupaten Bangka - Zulfan Yus Andi; Yuliyanto Yuliyanto (Manutech : Jurnal Teknologi Manufaktur, 2017)
Lakso is one of product’s traditional that made from rice flour served with coconut milk, than mixed of fish meat. Lakso always provided available in stores, events, hotels. Stage of make it from preparation of materials, mixing, molding, make kuah lakso, and ready for eating. Lakso is selling at a price of Rp.3.000 sd. Rp. 5.000 per portion and sell for drying lakso at Rp. 80,000 /kg. Objectives of IbM, to improve quality and production capacity, so be able to improve at partner business management. From survey in 5 month ago, production in lakso has not been met and can not be enough for 75-80% wet’s lakso and 1% for dry’s lakso per month. Issues on partners, there are the production equipment, moulding of lakso and drying (heating from Sun). Other issues concerning the management of lakso provision, or sales. The achievements produced, the cooperation of UKM’s Pak Umar with Polmanbabel, implementation for Polmanbabel’s Tri Dharma that supply machine’s drying for capacity at 4 - 5 kg (rotary rak’s tray system, and aluminum material), research and Community Service by Lecturers and students. The results of activities are understanding, operation and maintenance of production in machine’s provided. the achievement of percentage for drying lakso until 80% and lakso able to survive up to 3 months. Lakso’s dry is able to eat by steaming process.